ToT Khatib as an Effort to Improve Leadership and Communication Skills in Islamic Economic and Financial Da'wah - Fakhry Hafiyyan Kurniawan; Edi Suryadi; Jannah Sojannah; Eeng Ahman; Winny Astiwardhani; Mahbub Afini Maulana (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The Khatib (Friday prayer preachers) Training of Trainers (ToT) activity conducted by Bank Indonesia Representative Office of West Java Province is aimed at improving the leadership and communication skills of Khatib in West Java Province in improving the level of Islamic economics and finance (Eksyar) understanding. The participants of this activity were 300 people consisting of Islamic boarding school representatives, Islamic community organizations, and the Indonesian Mosque Council of West Java Province. One of the challenges in Eksyar development is related to the low understanding or literacy of the community regarding Eksyar which was only 9.14% and the weak market share of Islamic economics when compared to conventional economics nationally. The key success of this Khatib ToT is the competency of speakers and the time efficiency given by the committee so that the activity was carried out in a comprehensive manner for 1 (one) day. In developing the program, collaboration with vertical and horizontal institutions was needed such as OJK, KNEKS, KDEKS of West Java Province, PT. Bank Syariah Indonesia, Tbk., MES of West Java Province, academics, and other stakeholders. Increasing understanding of Eksyar literacy is expected to encourage Indonesia's potential globally related to the development of the sharia industry.